HATE SPEECH UNDER INTERNATIONAL AND NATIONAL LAWS: A COMPARATIVE ANALYSIS FROM ISLAMIC LAW PERSPECTIVE - Islam, Zahidul; Norullah (International Journal of Psychosocial Rehabilitation, 2020)
Hate speech and expression is considered as one of the burning issues of the current socio- political world. The approaches of international and national laws are generally different from Islamic law in the subject. The formal laws commonly provide infinitive freedom while Islamic law wants some limits up on it. In other words, international and national laws represent unbounded freedom of speech with nominal legal restrictions whereas Islamic concept of freedom of expression has various moral and legal bindings based on divine ethics to protect freedom of expression and individual rights and not to curb the acts of civil and religious defamation. Hence, the legal constraints in international and national laws are insufficient because they legalese unlimited freedom of speech and their legal restrictions are also either partial or nonexistent. This article is a comparative desiccation which examines international, national and Islamic laws to protect people from hate speech and expression. The study follows qualitative approach to discuss the issues and analyses data. Basically, secondary resources are used in this paper, thus information has been taken from articles, book, newspapers, case laws and status. This study finds that the freedom of speech and expression is a fundamental human right which must be achieved through certain essential objectives like disclosure of truth and the honour of human beings.